ANALISIS DU PONT SYSTEM DENGAN TIME SERIES APPROACH (TSA) DAN CROSS SECTIONAL APPROACH (CSA) DALAM PENILAIAN KINERJA KEUANGAN PERUSAHAAN (Industri Food and Beverages yang terdaftar di Bursa Efek Indonesia periode 2016-2020): Du Pont System, Penilaian Kinerja, Time Series Approach, Cross Sectional Approach - Adhitrie, Ni Nyoman Narayani; Diatmika, I Putu Gede (Universitas Pendidikan Ganesha, 2021)
This study was conducted to determine the Financial Performance Assessment of Food and Beverages Industry Companies listed on the Indonesia Stock Exchange for the 2016-2020 period based on the Du Pont System analysis method with Time Series Approach (TSA) and Cross Sectional Approach (CSA). This study uses a descriptive method with a quantitative approach. The population and sample in this study were obtained on the Indonesia Stock Exchange for the 2016-2020 period. The research data collection method used the documentation method and the non-participatory observation method. After the data is obtained, the Total Asset Turnover, NPM Equity Multiplier and ROI are determined, then compared with Time Series Aproach (TSA) analysis and Cross Sectional Aproach (CSA) analysis in order to obtain conclusions. The results of this study state that Akasha Wira Internasional Tbk, Indofood Sukses Makmur Tbk, and Wilmar Cahaya Indonesia Tbk are above the industry average value of 0.67% so that it can be said to perform well in the Time Series Approach and Cross Sectioal Approach during the 2016-2020 period. . Meanwhile, Tiga Pilar Sejahtera Food Tbk, Delta Djakarta Tbk, Campina Ice Cream Industry Tbk and Ultra Jaya Milk Industry & Trading Company Tbk were below above the industry average value of 0.67% so it could be said that they performed poorly in Time Series Approach and Cross. Sectioal Approach during the 2016-2020 period.